Biodegradable geotextile and preparation method thereof

By using bio-based materials such as cellulose, polylactic acid and PBAT, the problem of difficult degradation of existing geotextiles is solved, and the effect of safety, environmental protection and easy degradation is achieved, meeting temporary civil engineering needs and reducing recycling costs.

CN119592031APending Publication Date: 2025-03-11CHINA CHEM DONGHUA TIANYE NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411840118.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Most of the existing geotextile materials are polymeric fibers, which have good stability but are difficult to degrade. Burying them on the ground for a long time will cause environmental pollution and soil damage, and the recycling cost is high.

Method used

Bio-based materials such as cellulose, polylactic acid and PBAT, combined with compatibility agents, antioxidants, lubricants and opening additives, are prepared by modified granulation and blown film through a twin-screw extruder to obtain biodegradable geotextile.

Benefits of technology

The safety, environmental protection and degradability of geotextiles are achieved, and they meet the needs of temporary civil engineering. They can be completely degraded after the project is completed, without negative impact on the environment and soil quality, reducing recycling costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005187768780000081
    Figure BDA0005187768780000081
  • Figure BDA0005187768780000091
    Figure BDA0005187768780000091
  • Figure BDA0005187768780000092
    Figure BDA0005187768780000092
Patent Text Reader

Abstract

The invention relates to biodegradable geotechnical cloth and a preparation method thereof. The biodegradable geotextile is prepared from the following raw materials in parts by weight: 20 to 30 parts of cellulose, 10 to 20 parts of PBAT, 50 to 70 parts of polylactic acid, 0.5 to 2 parts of a compatilizer, 0.2 to 0.8 part of an antioxidant, 1 to 5 parts of a lubricant and 0.5 to 2 parts of an anti-blocking agent. According to the biodegradable geotextile and the preparation method thereof disclosed by the invention, the cellulose / PBAT / polylactic acid biodegradable geotextile is prepared, is safe and environment-friendly, is easy to degrade, and can meet the requirements of temporary civil engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer materials, and in particular relates to a biodegradable geotextile and a preparation method thereof. Background Art

[0002] Geotextile is a new type of building material used in civil engineering. It is usually processed and produced with polypropylene, polyester, spandex, nylon or synthetic fibers. It has multiple functions such as filtration, anti-filtration, isolation, reinforcement, protection, and sealing. It is widely used in drainage of artificial fill foundations, water well filter layers in water conservancy projects, isolation layers between road embankments and roadbeds, and reinforcement in earth wall backfill. At present, most of the geotextile materials used in China are polymer fibers. Most of them have good stability and are not easy to degrade. They will not completely rot even if buried in the soil for decades or hundreds of years. For some temporary projects, the geotextile needs to be recycled after the project is completed, which invisibly increases the cost of the project. If it is not recycled, the degraded harmful substances will pollute the environment and even cause irreversible damage to the soil. The use of biodegradable geotextiles can meet the use requirements during the project period. After the project is completed, it will be completely degraded, and the decomposition products are water and carbon dioxide, which will not have a negative impact on the environment and soil.

[0003] In view of this, the present invention proposes a new biodegradable geotextile and a preparation method thereof. The geotextile is safe, environmentally friendly, and easily degradable, and can meet the needs of temporary civil engineering projects. Summary of the invention

[0004] The invention aims to provide a biodegradable geotextile, which is safe, environmentally friendly, easily degradable and can meet the needs of temporary civil engineering projects.

[0005] In order to achieve the above purpose, the technical solution adopted is:

[0006] A biodegradable geotextile is prepared using the following raw materials in parts by weight:

[0007] Cellulose 20-30 parts, PBAT 10-20 parts, polylactic acid 50-70 parts, compatibilizer 0.5-2 parts, antioxidant 0.2-0.8 parts, lubricant 1-5 parts, opening agent 0.5-2 parts.

[0008] Furthermore, the cellulose is activated cellulose.

[0009] The compatibilizer comprises: at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, epoxy chain extender ADR-4368, epoxy chain extender BP96, chain extender 6902, epoxy soybean oil, silane coupling agent KH560, silane coupling agent KH550, silane coupling agent KH570, glycidyl methacrylate, 4,4'-methylenebis(phenyl isocyanate), polyethylene glycol, benzoyl peroxide, acetylated tributyl citrate, glycidyl methacrylate grafted polyolefin elastomer, and maleic anhydride;

[0010] The lubricant comprises: at least one of PE wax, oxidized polyethylene wax, white oil, and stearic acid triglyceride;

[0011] The antioxidant comprises: at least one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant 168, and antioxidant 264;

[0012] The opening aid comprises at least one of oleamide, erucamide, EBS derivatives, silicon dioxide, talc and titanium dioxide;

[0013] The weight average molecular weight of the PBAT is 100,000-200,000, and the melt index is 3-10;

[0014] The weight average molecular weight of the polylactic acid is 60,000-100,000 and the melt index is 1-10.

[0015] Furthermore, the activated cellulose includes at least one of: CNC modified by grafting with polybutylene glutarate, CNC chemically modified with phenylbutyl isocyanate, CNC modified by grafting with octadecyl isocyanate, acetylated cellulose, and cellulose modified with a phthalate coupling agent, an aluminate coupling agent, or a silane coupling agent;

[0016] The compatibilizer is a compound of at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, and silane coupling agent KH560 and acetylated tributyl citrate;

[0017] The lubricant is PE wax and stearic acid triglyceride;

[0018] The antioxidants are antioxidant 1010 and antioxidant 168;

[0019] The opening agent is erucamide or talcum powder;

[0020] The weight average molecular weight of the PBAT is 100,000-130,000, and the melt index is 3-5;

[0021] The weight average molecular weight of the polylactic acid is 70,000-80,000, and the melt index is 5-10.

[0022] Furthermore, the cellulose is acetylated cellulose;

[0023] The silicon dioxide is synthetic silicon dioxide, and the talc is ultrafine talc.

[0024] Furthermore, the particle size of the ultrafine talc powder is 5000-7000 mesh, and the titanium dioxide is nano-grade titanium dioxide.

[0025] Furthermore, the amount of the opening agent is 0.5-2% of the total amount of cellulose, polylactic acid, and PBAT;

[0026] The amount of the compatibilizer is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT;

[0027] The amount of the lubricant is 1-5% of the total amount of cellulose, polylactic acid and PBAT;

[0028] The dosage of the antioxidant is 0.2-0.8% of the total dosage of cellulose, polylactic acid and PBAT.

[0029] Another object of the present invention is to provide a method for preparing the above-mentioned biodegradable geotextile, which is simple and suitable for industrial operation.

[0030] In order to achieve the above purpose, the technical solution adopted is:

[0031] The method for preparing the above-mentioned biodegradable geotextile comprises the following steps:

[0032] Evenly mix cellulose, PBAT, polylactic acid, a compatibilizer, an antioxidant, a lubricant, and an opening agent to obtain a mixture;

[0033] The mixed material is added into a twin-screw extruder, extruded, pelletized and dried to obtain a cellulose / PBAT / polylactic acid modified resin;

[0034] The cellulose / PBAT / polylactic acid modified resin is blown into a film to obtain the biodegradable geotextile.

[0035] Further, the operating temperature of the twin-screw extruder is 100-180°C;

[0036] The operating temperature of the film blowing is 100-180°C;

[0037] The water content of the cellulose / PBAT / polylactic acid modified resin does not exceed 500 ppm.

[0038] Furthermore, the screw feeding speed of the twin-screw extruder is 50-500RPM, the pelletizer traction speed is 10-100RPM, and the aspect ratio of the screw is 25-55:1.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] 1. The technical solution of the present invention uses cellulose, polylactic acid and PBAT as base materials, and with the assistance of compatibilizer, antioxidant, lubricant and opening aid, undergoes twin-screw modification and granulation, and then adds the modified resin into a film blowing machine for film blowing to obtain a modified material product of a degradable geotextile that meets the processing requirements. The performance of the modified material product of the degradable geotextile can meet the needs of laying temporary civil engineering and construction projects, and improves the environmental protection and safety of the national infrastructure construction process.

[0041] 2. The technical solution of the present invention adopts cellulose as the base material, and the addition of cellulose reduces the production cost.

[0042] 3. The technical solution of the present invention has a simple preparation method and is suitable for industrial operation. DETAILED DESCRIPTION

[0043] In order to further explain the biodegradable geotextile and its preparation method of the present invention and achieve the intended purpose of the invention, the following is a detailed description of the biodegradable geotextile and its preparation method according to the present invention, its specific implementation method, structure, characteristics and efficacy, in combination with the preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.

[0044] The following will further introduce a biodegradable geotextile and its preparation method in detail in conjunction with specific embodiments of the present invention:

[0045] The present invention provides a biodegradable geotextile and a preparation method thereof. The groups on the cellulose, PLA and PBAT molecular chains undergo a cross-linking reaction under the shearing action of a twin-screw extruder, and are modified and granulated to fully utilize the good softness and ductility of the PBAT molecular chain segments to improve the toughness and impact resistance of the composite material. The cellulose / PBAT / polylactic acid biodegradable geotextile prepared by the present invention is safe, environmentally friendly, and easily degradable, and can meet the needs of temporary civil engineering projects. The technical solution adopted by the present invention is:

[0046] A biodegradable geotextile is prepared using the following raw materials in parts by weight:

[0047] Cellulose 20-30 parts, PBAT 10-20 parts, polylactic acid 50-70 parts, compatibilizer 0.5-2 parts, antioxidant 0.2-0.8 parts, lubricant 1-5 parts, opening agent 0.5-2 parts.

[0048] Preferably, the cellulose is activated cellulose.

[0049] Further preferably, the activated cellulose includes: cellulose nanocrystals (CNC) modified by grafting polybutylene glutarate, CNC chemically modified by phenylbutyl isocyanate, CNC grafted and modified by octadecyl isocyanate, acetylated cellulose (CNS), and at least one of cellulose modified by phthalate coupling agent, aluminate coupling agent, or silane coupling agent.

[0050] More preferably, the cellulose is acetylated cellulose (CNS).

[0051] Preferably, the compatibilizer includes: at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, epoxy chain extender ADR-4368, epoxy chain extender BP96, chain extender 6902, epoxy soybean oil, silane coupling agent KH560, silane coupling agent KH550, silane coupling agent KH570, glycidyl methacrylate, 4,4'-methylenebis(phenyl isocyanate), polyethylene glycol, benzoyl peroxide, acetylated tributyl citrate, glycidyl methacrylate grafted polyolefin elastomer, and maleic anhydride.

[0052] Further preferably, the compatibilizer is a compound of at least one of epoxy chain extender ADR4468, epoxy chain extender ADR370, and silane coupling agent KH560 and acetylated tributyl citrate in equal amounts.

[0053] Preferably, the lubricant comprises at least one of PE wax, oxidized polyethylene wax, white oil and stearic acid triglyceride.

[0054] Further preferably, the lubricant is a mixture of PE wax and stearic acid triglyceride of equal quality.

[0055] In the above technical solution, the present invention further limits the use of a lubricant compounded with PE wax and stearic acid triglyceride, wherein the PE wax reduces the friction between the material and the cavity and the screw, and the stearic acid triglyceride reduces the friction inside the material.

[0056] Preferably, the antioxidant includes at least one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant 168, and antioxidant 264.

[0057] Further preferably, the antioxidant is antioxidant B215 which is a compound of antioxidant 1010 and antioxidant 168 of equal quality.

[0058] Preferably, the opening aid comprises at least one of oleamide, erucamide, EBS derivatives, silicon dioxide, talc and titanium dioxide.

[0059] In the above technical scheme, the present invention mainly adopts organic opening agents (oleamide, erucamide, EBS derivatives) and inorganic opening agents (silicon dioxide, talc, titanium dioxide).

[0060] More preferably, the silicon dioxide is synthetic silicon dioxide, the talc is ultrafine talc with a particle size of 5000-7000 mesh, and the titanium dioxide is nano-grade titanium dioxide.

[0061] Further preferably, the opening agent is erucamide or talc.

[0062] Preferably, the weight average molecular weight of the PBAT is 100,000-200,000, and the melt index is 3-10;

[0063] The weight average molecular weight of the polylactic acid is 60,000-100,000 and the melt index is 1-10.

[0064] Further preferably, the weight average molecular weight of the PBAT is 100,000-130,000, and the melt index is 3-5;

[0065] The weight average molecular weight of the polylactic acid is 70,000-80,000, and the melt index is 5-10.

[0066] In the above technical solution, the requirements for weight average molecular weight and melt index of polylactic acid and PBAT are to ensure the fluidity of the raw materials during the preparation process.

[0067] Preferably, the amount of the opening agent is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT;

[0068] The amount of the compatibilizer is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT;

[0069] The amount of the lubricant is 1-5% of the total amount of cellulose, polylactic acid and PBAT;

[0070] The dosage of the antioxidant is 0.2-0.8% of the total dosage of cellulose, polylactic acid and PBAT.

[0071] The method for preparing the above-mentioned biodegradable geotextile comprises the following steps:

[0072] Evenly mix cellulose, PBAT, polylactic acid, a compatibilizer, an antioxidant, a lubricant, and an opening agent to obtain a mixture;

[0073] The mixed material is added into a twin-screw extruder, extruded, pelletized and dried to obtain a cellulose / PBAT / polylactic acid modified resin;

[0074] The cellulose / PBAT / polylactic acid modified resin is blown into a film to obtain the biodegradable geotextile.

[0075] Preferably, the base material and the auxiliary agent are added to the mixer in a certain order, and the order of addition is granular material, powder, and liquid material, which is more conducive to sufficient mixing.

[0076] Preferably, the operating temperature of the twin-screw extruder is 100-180°C;

[0077] The operating temperature of the film blowing is 100-180°C;

[0078] The water content of the cellulose / PBAT / polylactic acid modified resin does not exceed 500 ppm.

[0079] Preferably, the screw feeding speed of the twin-screw extruder is 50-500RPM, the pelletizer traction speed is 10-100RPM, and the aspect ratio of the screw is 25-55:1.

[0080] "Parts" in the examples refer to "parts by weight".

[0081] The PBAT with the brand name DT-10A produced by China Chemical Donghua Tianye New Materials Co., Ltd. in the embodiment has a weight average molecular weight of 100,000-200,000 and a melt index of 3-10; the PLA with the brand name DT-10A produced by Donghua Tianren has a weight average molecular weight of 60,000-100,000 and a melt index of 1-10.

[0082] The antioxidant B215 in the embodiment is prepared by compounding antioxidant 1010 and antioxidant 168 of equal mass.

[0083] The raw materials not described in detail in this embodiment can be purchased from the market, and the treatments not described in detail adopt mature conventional means in the prior art and are common knowledge in the art.

[0084] Example 1.

[0085] The specific steps are as follows:

[0086] (1) Weigh 20-30 parts of cellulose, 10-20 parts of PBAT, 50-70 parts of polylactic acid, 0.5-2 parts of compatibilizer, 0.2-0.8 parts of antioxidant, 1-5 parts of lubricant, and 0.5-2 parts of anti-blocking agent.

[0087] The cellulose is activated cellulose.

[0088] The compatibilizer includes: at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, epoxy chain extender ADR-4368, epoxy chain extender BP96, chain extender 6902, epoxy soybean oil, silane coupling agent KH560, silane coupling agent KH550, silane coupling agent KH570, glycidyl methacrylate, 4,4'-methylenebis(phenyl isocyanate), polyethylene glycol, benzoyl peroxide, acetylated tributyl citrate, glycidyl methacrylate grafted polyolefin elastomer, and maleic anhydride;

[0089] The lubricant comprises: at least one of PE wax, oxidized polyethylene wax, white oil, and stearic acid triglyceride;

[0090] The antioxidant includes at least one of antioxidant 1010 , antioxidant 1076 , antioxidant CA, antioxidant 164 , antioxidant 168 , and antioxidant 264 .

[0091] The opening aid comprises at least one of oleamide, erucamide, EBS derivatives, silicon dioxide, talc and titanium dioxide;

[0092] The weight average molecular weight of PBAT is 100,000-200,000, and the melt index is 3-10;

[0093] The weight average molecular weight of the polylactic acid is 60,000-100,000 and the melt index is 1-10.

[0094] Preferably, the activated cellulose includes: CNC modified by grafting with polybutylene glutarate, CNC chemically modified with phenylbutyl isocyanate, CNC modified by grafting with octadecyl isocyanate, acetylated cellulose, and cellulose modified with a phthalate coupling agent, an aluminate coupling agent, or a silane coupling agent;

[0095] The compatibilizer is a compound of at least one of epoxy chain extender ADR4468, epoxy chain extender ADR370, and silane coupling agent KH560 and acetylated tributyl citrate;

[0096] The lubricants are PE wax and stearic acid triglyceride;

[0097] The antioxidant is antioxidant B215 which is a compound of antioxidant 1010 and antioxidant 168 of equal quality;

[0098] The opening agent is erucamide or talcum powder.

[0099] The weight average molecular weight of the PBAT is 100,000-130,000, and the melt index is 3-5;

[0100] The weight average molecular weight of the polylactic acid is 70,000-80,000, and the melt index is 5-10.

[0101] Further preferably, the cellulose is acetylated cellulose;

[0102] The silicon dioxide is synthetic silicon dioxide, the talc is ultrafine talc with a particle size of 5000-7000 mesh, and the titanium dioxide is nano-grade titanium dioxide.

[0103] Further preferably, the amount of the opening agent is 0.5-2% of the total amount of cellulose, polylactic acid, and PBAT;

[0104] The amount of compatibilizer is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT;

[0105] The amount of lubricant used is 1-5% of the total amount of cellulose, polylactic acid, and PBAT;

[0106] The dosage of the antioxidant is 0.2-0.8% of the total dosage of cellulose, polylactic acid and PBAT.

[0107] (2) Add the raw materials into a high-speed mixer in a certain order, namely, granular material, powder, and liquid material. Turn the mixing speed to high speed, mix at high speed until uniform, and then discharge the materials to obtain a mixed material.

[0108] (3) Add the mixed material into the hopper of the twin-screw extruder, the screw feeding speed of the twin-screw extruder is 50-500RPM, the pelletizer pulling speed is 10-100RPM, and the aspect ratio of the screw is 25-55:1. Set the temperature zones of the twin-screw extruder, the operating temperature is 100-180°C, and after stranding and pelletizing, a cellulose / PBAT / polylactic acid modified resin, referred to as PBAT modified resin, can be obtained.

[0109] The temperature setting principle of each temperature zone of the twin-screw extruder is a general principle in the art, which ensures the fluidity, dispersibility and non-degradation of the raw materials while allowing the raw materials to fully react. The temperature setting method is also a conventional method in the art. After thermogravimetric analysis, the degradation temperature is determined, thereby determining the appropriate temperature. The operating temperature of each temperature zone of the twin-screw extruder of the present invention is 100-180°C.

[0110] (4) Place the PBAT modified resin in a drying oven, set the temperature to 80°C, and dry for about 8 hours until the moisture content of the resin is ≤500ppm.

[0111] (5) The dried PBAT modified resin is placed in a film blowing machine for film blowing, and the operating temperature of each temperature zone of the film blowing machine is 100-180° C. (the temperature setting principle and method of each temperature zone of the film blowing machine are the same as those of the twin-screw extruder), and finally a fully biodegradable film, namely the biodegradable geotextile, is obtained.

[0112] Example 2.

[0113] The specific raw materials and dosage are shown in Table 1

[0114] Table 1

[0115]

[0116]

[0117] The specific steps are as follows:

[0118] (1) Weigh the raw materials according to Table 1.

[0119] (2) Add the raw materials into a high-speed mixer in a certain order, the order of addition is PBAT, cellulose, PLA, ADR4468, B215, PE wax, stearic acid triglyceride, erucamide, and turn the mixing speed to high speed. After high-speed mixing for about 10 minutes, the material can be discharged to obtain a mixture.

[0120] (3) Add the mixed material into the hopper of the twin-screw extruder. The screw feeding speed of the twin-screw extruder is 200RPM, the pelletizer pulling speed is 50RPM, and the screw length-diameter ratio is 40:1. Set the temperature zones of the twin-screw extruder, the operating temperature is 100-180°C, and after stranding and pelletizing, PBAT modified resin can be obtained.

[0121] (4) Place the PBAT modified resin in a drying oven, set the temperature to 80°C, and dry for about 8 hours until the moisture content of the resin is ≤200ppm.

[0122] (5) The dried PBAT modified resin is placed in a film blowing machine for film blowing. The operating temperature of each temperature zone of the film blowing machine is 100-180° C., and finally a fully biodegradable film, i.e., a biodegradable geotextile, is obtained.

[0123] Example 3.

[0124] The specific operation steps are the same as those in Example 2, except that the raw materials and amounts are shown in Table 2.

[0125] Table 2

[0126]

[0127]

[0128] The specific operation steps are the same as those in Example 2.

[0129] Example 4.

[0130] The specific operation steps are the same as those in Example 2, except that the raw materials and amounts are shown in Table 3.

[0131] Table 3

[0132]

[0133] Example 5.

[0134] The specific operation steps are the same as those in Example 2, except that the raw materials and amounts are shown in Table 4.

[0135] Table 4

[0136]

[0137]

[0138] Comparative Example 1.

[0139] The specific operation steps are the same as those in Example 2, except that the raw materials and amounts are shown in Table 5.

[0140] Table 5

[0141]

[0142] Example 6.

[0143] The biodegradable geotextiles prepared in Examples 2-5 and Comparative Example 1 were sampled and their properties were tested. The results are shown in Table 6.

[0144] Table 6 Blown film test results

[0145] Element Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Tensile strength(MPa) 44 40 37.6 38.5 40.5 Elongation at break (%) 125 85 145 118 75

[0146] It can be seen from Table 6 that the addition of PBAT significantly increases the elongation at break, so that the biodegradable geotextile prepared by the present invention can meet the laying needs of temporary civil engineering and construction projects.

[0147] Example 7.

[0148] The specific operation steps are the same as those in Example 3, except that the raw materials and amounts are shown in Table 7.

[0149] Table 7

[0150]

[0151] The specific operation steps are the same as those in Example 3.

[0152] Example 8.

[0153] The specific operation steps are the same as those in Example 3, except that the raw materials and amounts are shown in Table 8.

[0154] Table 8

[0155]

[0156]

[0157] The specific operation steps are the same as those in Example 3.

[0158] Example 9.

[0159] The specific operation steps are the same as those in Example 3, except that the epoxy chain extender ADR4370 replaces the epoxy chain extender ADR4468, as shown in Table 9.

[0160] Table 9

[0161]

[0162] The specific operation steps are the same as those in Example 3.

[0163] Example 10.

[0164] The specific operation steps are the same as those in Example 3, except that the silane coupling agent KH560 replaces the epoxy chain extender ADR4468, as shown in Table 10.

[0165] Table 10

[0166]

[0167]

[0168] The specific operation steps are the same as those in Example 3.

[0169] Example 11.

[0170] The specific operation steps are the same as those in Example 3, except that the lubricant oxidized polyethylene wax replaces the PE wax, as shown in Table 11.

[0171] Table 11

[0172]

[0173] The specific operation steps are the same as those in Example 3.

[0174] Example 12.

[0175] The specific operation steps are the same as those in Example 3, except that lubricant white oil replaces PE wax, and the raw materials and amounts are specifically shown in Table 12.

[0176] Table 12

[0177]

[0178] The specific operation steps are the same as those in Example 3.

[0179] Example 13.

[0180] The specific operation steps are the same as those in Example 3, except that the anti-blocking agent talcum powder replaces erucamide, as shown in Table 13.

[0181] Table 13

[0182]

[0183] The specific operation steps are the same as those in Example 3.

[0184] Example 14.

[0185] The biodegradable geotextiles prepared in Examples 7-13 and Example 3 were sampled and their properties were tested. The results are shown in Table 14.

[0186] Table 14 Blown film test results

[0187] Example Tensile strength(MPa) Elongation at break (%) Number of film blowing crystal points / ㎡ Example 3 37.6 145 0 Example 7 36.5 138 0 Example 8 36.8 135 0 Example 9 35.5 126 5 Example 10 35.5 133 5 Embodiment 11 36.3 143 3 Example 12 35.8 138 5 Embodiment 13 38.3 122 8

[0188] From Table 14, it can be seen that the embodiments of the present invention use activated cellulose, PBAT, and polylactic acid as base materials, epoxy chain extender ADR4468 as the main compatibilizer, acetylated tributyl citrate (ATBC) as the auxiliary compatibilizer, B215 compounded with antioxidant 1010 and antioxidant 168 as the antioxidant, PE wax as the external lubricant, stearic acid triglyceride as the internal lubricant, erucamide / talc as the opening agent, and carry out twin-screw modification and granulation, and then add the modified resin into the film blowing machine for film blowing, and obtain the modified material product of the degradable geotextile that can meet the processing requirements by detecting relevant indicators.

[0189] Example 15.

[0190] The specific raw materials and amounts are shown in Table 15.

[0191] Table 15

[0192]

[0193]

[0194] The specific steps are as follows:

[0195] (1) Weigh the raw materials according to Table 15.

[0196] (2) Add the raw materials into a high-speed mixer in a certain order, namely, granular material, powder, and liquid material. Turn the mixing speed to high speed and mix at high speed for about 20 minutes before discharging the material to obtain a mixed material.

[0197] (3) Add the mixed material into the hopper of the twin-screw extruder. The screw feeding speed of the twin-screw extruder is 50RPM, the pelletizer pulling speed is 10RPM, and the screw length-diameter ratio is 25:1. Set the temperature zones of the twin-screw extruder, the operating temperature is 100-180°C, and after stranding and pelletizing, PBAT modified resin can be obtained.

[0198] (4) Place the PBAT modified resin in a drying oven, set the temperature to 80°C, and dry for about 8 hours until the moisture content of the resin is ≤300ppm.

[0199] (5) The dried PBAT modified resin is placed in a film blowing machine for film blowing. The operating temperature of each temperature zone of the film blowing machine is 100-180° C. to obtain a biodegradable geotextile.

[0200] Example 16.

[0201] The specific raw materials and amounts are shown in Table 16.

[0202] Table 16

[0203]

[0204]

[0205] The specific steps are as follows:

[0206] (1) Weigh the raw materials according to Table 16.

[0207] (2) Add the raw materials into a high-speed mixer in a certain order, namely, granular material, powder, and liquid material. Turn the mixing speed to high speed and mix at high speed for about 20 minutes before discharging the material to obtain a mixed material.

[0208] (3) Add the mixed material into the hopper of the twin-screw extruder. The screw feeding speed of the twin-screw extruder is 500RPM, the pelletizer pulling speed is 100RPM, and the aspect ratio of the screw is 55:1. Set the temperature zones of the twin-screw extruder, the operating temperature is 100-180°C, and after stranding and pelletizing, PBAT modified resin can be obtained.

[0209] (4) Place the PBAT modified resin in a drying oven, set the temperature to 80°C, and dry for about 8 hours until the moisture content of the resin is ≤200ppm.

[0210] (5) The dried PBAT modified resin is placed in a film blowing machine for film blowing. The operating temperature of each temperature zone of the film blowing machine is 100-180° C. to obtain a biodegradable geotextile.

[0211] Example 17.

[0212] The specific raw materials and amounts are shown in Table 17.

[0213] Table 17

[0214]

[0215]

[0216] The specific steps are as follows:

[0217] (1) Weigh the raw materials according to Table 17.

[0218] (2) Add the raw materials into a high-speed mixer in a certain order, namely, granular material, powder, and liquid material. Turn the mixing speed to high speed and mix at high speed for about 15 minutes before discharging the material to obtain a mixed material.

[0219] (3) Add the mixed material into the hopper of the twin-screw extruder. The screw feeding speed of the twin-screw extruder is 200RPM, the pelletizer pulling speed is 40RPM, and the length-to-diameter ratio of the screw is 30:1. Set the temperature zones of the twin-screw extruder to an operating temperature of 100-170°C. After stranding and pelletizing, PBAT modified resin can be obtained.

[0220] (4) Place the PBAT modified resin in a drying oven, set the temperature to 80°C, and dry for about 8 hours until the moisture content of the resin is ≤250ppm.

[0221] (5) The dried PBAT modified resin is placed in a film blowing machine for film blowing. The operating temperature of each temperature zone of the film blowing machine is 100-170° C. to obtain a biodegradable geotextile.

[0222] The above is only a preferred embodiment of the embodiment of the present invention, and does not impose any form of limitation on the embodiment of the present invention. Any simple modification, equivalent changes and modifications made to the above embodiment based on the technical essence of the embodiment of the present invention are still within the scope of the technical solution of the embodiment of the present invention.

Claims

1. A biodegradable geotextile, characterized in that: It is prepared using the following raw materials in parts by weight: Cellulose 20-30 parts, PBAT 10-20 parts, polylactic acid 50-70 parts, compatibilizer 0.5-2 parts, antioxidant 0.2-0.8 parts, lubricant 1-5 parts, opening agent 0.5-2 parts.

2. The biodegradable geotextile according to claim 1, characterized in that: The cellulose is activated cellulose; The compatibilizer comprises: at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, epoxy chain extender ADR-4368, epoxy chain extender BP96, chain extender 6902, epoxy soybean oil, silane coupling agent KH560, silane coupling agent KH550, silane coupling agent KH570, glycidyl methacrylate, 4,4'-methylenebis(phenyl isocyanate), polyethylene glycol, benzoyl peroxide, acetylated tributyl citrate, glycidyl methacrylate grafted polyolefin elastomer, and maleic anhydride; The lubricant comprises: at least one of PE wax, oxidized polyethylene wax, white oil, and stearic acid triglyceride; The antioxidant comprises: at least one of antioxidant 1010, antioxidant 1076, antioxidant CA, antioxidant 164, antioxidant 168, and antioxidant 264; The opening aid comprises at least one of oleamide, erucamide, EBS derivatives, silicon dioxide, talc and titanium dioxide; The weight average molecular weight of the PBAT is 100,000-200,000, and the melt index is 3-10; The weight average molecular weight of the polylactic acid is 60,000-100,000 and the melt index is 1-10.

3. The biodegradable geotextile according to claim 2, characterized in that: The activated cellulose includes at least one of CNC modified by grafting polybutylene glutarate, CNC chemically modified by phenylbutyl isocyanate, CNC modified by grafting octadecyl isocyanate, acetylated cellulose, and cellulose modified by phthalate coupling agent, aluminate coupling agent, or silane coupling agent; The compatibilizer is a compound of at least one of epoxy chain extender ADR4468, epoxy chain extender ADR4370, and silane coupling agent KH560 and acetylated tributyl citrate; The lubricant is PE wax and stearic acid triglyceride; The antioxidants are antioxidant 1010 and antioxidant 168; The opening agent is erucamide or talcum powder; The weight average molecular weight of the PBAT is 100,000-130,000, and the melt index is 3-5; The weight average molecular weight of the polylactic acid is 70,000-80,000, and the melt index is 5-10.

4. The biodegradable geotextile according to claim 3, characterized in that: The cellulose is acetylated cellulose; The silicon dioxide is synthetic silicon dioxide, and the talc is ultrafine talc.

5. The biodegradable geotextile according to claim 4, characterized in that: The particle size of the ultrafine talc powder is 5000-7000 mesh, and the titanium dioxide is nano-grade titanium dioxide.

6. The biodegradable geotextile according to claim 1, characterized in that: The amount of the opening agent is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT; The amount of the compatibilizer is 0.5-2% of the total amount of cellulose, polylactic acid and PBAT; The amount of the lubricant is 1-5% of the total amount of cellulose, polylactic acid and PBAT; The dosage of the antioxidant is 0.2-0.8% of the total dosage of cellulose, polylactic acid and PBAT.

7. The method for preparing the biodegradable geotextile according to any one of claims 1 to 6, characterized in that: The following steps are involved: Evenly mix cellulose, PBAT, polylactic acid, a compatibilizer, an antioxidant, a lubricant, and an opening agent to obtain a mixture; The mixed material is added into a twin-screw extruder, extruded, pelletized and dried to obtain a cellulose / PBAT / polylactic acid modified resin; The cellulose / PBAT / polylactic acid modified resin is blown into a film to obtain the biodegradable geotextile.

8. The preparation method according to claim 7, characterized in that: The operating temperature of the twin-screw extruder is 100-180°C; The operating temperature of the film blowing is 100-180°C; The water content of the cellulose / PBAT / polylactic acid modified resin does not exceed 500 ppm.

9. The preparation method according to claim 7, characterized in that: The screw feeding speed of the twin-screw extruder is 50-500RPM, the pelletizer pulling speed is 10-100RPM, and the aspect ratio of the screw is 25-55:1.